Faktor-Faktor Yang Mempengaruhi Perkembangan Bahasa Pada Anak Prasekolah - Hinggil Sri Rahayu; Rizki Amalia; Eka Rahmawati; Sri Handayani (JURNAL KESEHATAN TERAPAN, 2026)
According to the World Health Organization (WHO), approximately 43% of children under five years of age in low- and middle-income countries are at risk of not reaching their full developmental potential, including in the domains of language, cognitive, motor, and socio-emotional development (WHO, 2021). This condition is influenced by several factors, including poverty, malnutrition, inadequate stimulation, and non-responsive caregiving. The WHO emphasizes the importance of early childhood interventions, such as responsive caregiving and early learning opportunities, to promote optimal child growth and development..This study aims to examine the association between gadget use, parenting style, and gender with language development among preschool children at TKIT Rabbani, Muara Enim Regency, in 2025. An analytical observational design with a cross-sectional approach was employed. The study population comprised 245 children, with 71 respondents selected through accidental sampling. Primary data were collected and analyzed using univariate and bivariate analyses with the Chi-Square test, applying a significance level of α ≤ 0.05.The findings revealed a significant correlation between language development and gadget use (ρ = 0.000), parenting style (ρ = 0.000), and gender (ρ = 0.000). These results underscore the critical role of educational institutions in implementing effective language stimulation strategies, fostering parental engagement, and promoting responsible gadget use both at home and within school settings.